Water Dynamics in Competitive Solvation Assisted Loading of Colloidal Curcumin Nanoparticles onto Mesoporous Silica Nanostructures (Part. Part. Syst. Charact. 8/2022). (19th August 2022) - Ananth, A. Nitthin; Nagarajan, V.; Kumar, S. Suresh; Sasikumar, P.; Chirico, Giuseppe; D'Alfonso, Laura; Jose, Sujin P.
Abstract : In article number 2200062, Nitthin Ananth, Jose, and co‐workers studied that the sequential solvent evaporation approach combined with dielectric nano environment tuning mediates the uploading of hydrophobic curcumin nanoparticles onto mesoporous silica. The co‐solvents that modulate the water dynamics favor the form of monodispersed, stable nanostructures with high loading fractions.